A study of the use of discourse markers in a teenager with Tuberous sclerosis complex - Galdeano, María José; Guillén Escamilla, Josaphat Enrique; Fitta García, José de Jesús (Revista de Investigación en Logopedia, 2020)
The Tuberous Sclerosis Complex (TSC) is a genetic disorder that affects differentiation, proliferation, and cell migration in the first years of development, this causes a wide variety of hamartomatous lesions that can affect virtually any organ in the body, especially: skin, brain, lungs, kidneys, heart, and eyes. In this context, it is expected that people with TSC present various behavioral, cognitive and linguistic alterations. Regarding language alterations, there are currently few studies interested in describing these deficits, especially those that focus on the description of language per se. Therefore, in this research we analyze the linguistic production, specifically the use of discourse markers, of a teenager diagnosed with TSC through spontaneous speech. The results show that, in our patient, the use of discourse markers is maintained and used in a conventional way, with argumentative connectors, metadiscursives, reformulators, formulators and modalizers being the most used.